Case Report: Occult ocular toxocariasis revealed during vitrectomy in a child with chronic vitritis and vitreoretinal traction - Jing Chen; Ling Zhang (Frontiers in Medicine, 2026)
This report describes an 11-year-old girl who presented with a 6-month history of decreased visual acuity in the left eye without ocular pain or redness. She had a history of exposure to cats and dogs. Initial ophthalmic examination showed dense vitreous inflammatory opacities and diffuse fibroproliferative traction involving the posterior pole, but no typical granulomatous lesion was visible before surgery. The patient underwent 25-gauge pars plana vitrectomy with membrane peeling, and periocular triamcinolone acetonide (40 mg) was administered at the end of surgery for residual intraocular inflammation. During surgery, a peripheral grayish-white granulomatous lesion with associated retinal traction was identified. Paired serum and undiluted vitreous fluid testing showed elevated anti- Toxocara IgG levels, and the Goldmann–Witmer coefficient was markedly increased to 63.67, supporting local intraocular anti- Toxocara antibody production. Together with the intraoperative identification of a peripheral granulomatous lesion, these findings strongly supported the diagnosis of ocular toxocariasis. The postoperative course was uneventful, with no recurrent vitritis, new retinal lesion, retinal detachment, clinically evident macular edema, or progression of the peripheral granuloma during 12 months of follow-up. Anatomical stabilization was achieved, although visual recovery remained limited, likely because of long-standing tractional macular distortion and chronic structural damage. This case highlights that ocular toxocariasis should be considered in children with unilateral chronic vitritis and tractional vitreoretinal changes, even when a typical granuloma is not visible before surgery. Paired serum and undiluted vitreous antibody testing, together with calculation of the Goldmann–Witmer coefficient, can provide important diagnostic evidence, while vitrectomy may have both diagnostic and therapeutic value in advanced tractional cases.